Cellular and Molecular Regulation of Vaccination with Heat Shock Protein 60 from Histoplasma capsulatum - Deepe, Jr., George S. (American Society for Microbiology, 2002)
Vaccination with heat shock protein 60 (Hsp60) from Histoplasma capsulatum induces a protective immune response in mice. We explored the cellular and molecular requirements for the efficacy of recombinant Hsp60 in mice. Depletion of CD4(+), but not CD8(+), cells during the inductive phase of vaccination abolished protection, as assessed by survival and by the fungal burden in lungs and spleens. In the expressive phase, the elimination of CD4(+) or CD8(+) cells after immunization did not significantly alter fungal recovery or survival from a lethal challenge. Depletion of both subpopulations after Hsp60 vaccination resulted in a failure to control a lethal infection and a higher fungal burden in lungs and spleens. Cytokine release by spleen cells from mice vaccinated with Hsp60 produced substantially more gamma interferon and interleukin-10 and -12 than that of cells from mice immunized with either H. capsulatum recombinant Hsp70 or bovine serum albumin. The generation of gamma interferon, but not of interleukin-10, was dependent on T cells, in particular CD4(+) cells. Treatment of Hsp60-immunized mice with monoclonal antibody to gamma interferon or interleukin-10 or -12 in the inductive phase of vaccination was accompanied by increased recovery of yeast cells from lungs and spleens and 100% mortality. Likewise, the neutralization of gamma interferon or interleukin-12 abolished the protective effect of Hsp60 in the expressive phase. These results delineate the complexity of the regulatory elements necessary for vaccination against this fungus.